Issues in the application of e-wallet in Malaysia: a juristic analytical study - Mat Jubri@Shamsuddin, Mustafa; Sitiris, Miszairi; Mohd Yunus, Saidatolakma (Fakulti Ekonomi dan Muamalat, Universiti Sains Islam Malaysia, 2022)
The rapid growth of the financial industry in line with technological development leads to the emergence of e-wallet. E-wallet is an instrument of payment of goods or services electronically without the need to use cash. The use of e-wallet although still in its initial stages in Malaysia, is still subject to Shariah analysis. This study would like to analyze several Shariah issues in e-wallet, which aimed to measure the Shariah compliance, as well as to come out with some suggestions to improve its implementation. Among the research findings are the use of e-wallet is subject to origin of ruling in commercial transactions which is permissible, thus the Shariah analysis of it focuses on the circumstances that would make it forbidden, and the possible contracts between all contractors which include the user, the bank and non-bank issuer, and the third party have been discussed in the study with taking into consideration of conditions, and implications. Two methods will be used in this research, firstly the inductive method in collecting data, and the second is the analytical method in analyzing the data.